Hubungan antara Tingkat Pengetahuan dengan Sikap Ibu yang Memiliki Balita Stunting - Jayanti, Ni Ketut Parni; Suntari, Ni Luh Putu Yunianti (Jurnal Gema Keperawatan, 2024)
Stunting is a problem experienced by toddlers due to chronic malnutrition, causing the toddler’s height to be inappropriate for their age. Low maternal knowledge will influence the mother’s attitude in providing balanced nutrition to children. This research aims to determine the relationship between the level of knowledge and attitudes of mothers who have stunted toddlers at the UPTD Puskesmas Selat, Karangasem Regency in 2024. The research design used is a correlational analytical research type with a cross sectional approach. Sample selection used a total sampling technique with a sample size of 55 people. The data collection technique uses a questionnaire regarding knowledge and attitudes regarding stunting in toddlers. Data analysis used the Spearman rank test with α = 0.05. The results of this study showed that the majority of respondents had a good level of knowledge, 39 people (70.9%), 10 people had a sufficient level of knowledge (18.2%) and 6 people had a poor level of knowledge (10.9%). Respondents who had an attitude in the good category were 39 people (70,95), 9 people had an adequate attitude (16.4%) and 7 people had an attitude in the poor category (12.7%).The results of the Spearman rank correlation test obtained a p-value = 0.000 alpha 0.05, so the conclusion of this research is that there is a relationship between the level of knowledge and attitudes of mothers who have stunted toddlers at the UPTD Puskesmas Selat Karangasem Regency in 2024. Suggestion that health workers at the Community Health Center can support mothers, to increase their knowledge and attitudes about stunting prevention efforts.